2015
DOI: 10.1159/000438990
|View full text |Cite
|
Sign up to set email alerts
|

Folivory as a Constraint on Social Behaviour of Langurs in South India

Abstract: Folivory, being a dietary constraint, can affect the social time of colobines. In the present study, we compared food items and activity budgets of two closely related species of colobines inhabiting South India, i.e. the Hanuman langur (Semnopithecus hypoleucos) and Nilgiri langur (Semnopithecus johnii), to determine whether folivory had an impact on social time in these species. Our study established that Nilgiri langurs were more folivorous than Hanuman langurs. Nilgiri langurs spent much less time on socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Given the lower primary production of montane forests compared to forests at lower elevations with a different species composition [Whitten et al, 1996] population densities of primates on Java are lower at higher altitudes [Sugarjito et al 1997;Nijman, 2015]. The difference in structure and species composition between lowland and hill forest and montane forest reflects itself in pronounced differences in the diet of P. comata [Kavana et al, 2015;Yang et al, 2016]. Ruhiyat [1983] found the species to be largely folivorous at altitudes between 1,400 and 1,650 m a.s.l., with 65.2% of the diet comprising leaves and flowers (59.1% young leaves; 5.6% mature leaves, 7% flowers) and only 14.2% comprising fruits and seeds (13.5% fruit, 0.7% seeds).…”
Section: Discussionmentioning
confidence: 99%
“…Given the lower primary production of montane forests compared to forests at lower elevations with a different species composition [Whitten et al, 1996] population densities of primates on Java are lower at higher altitudes [Sugarjito et al 1997;Nijman, 2015]. The difference in structure and species composition between lowland and hill forest and montane forest reflects itself in pronounced differences in the diet of P. comata [Kavana et al, 2015;Yang et al, 2016]. Ruhiyat [1983] found the species to be largely folivorous at altitudes between 1,400 and 1,650 m a.s.l., with 65.2% of the diet comprising leaves and flowers (59.1% young leaves; 5.6% mature leaves, 7% flowers) and only 14.2% comprising fruits and seeds (13.5% fruit, 0.7% seeds).…”
Section: Discussionmentioning
confidence: 99%
“…The ideal gas model approach showed that primates in the Western Ghats do not form active associations with each other . In context to langurs, Hanuman Langurs are more social than Nilgiri Langurs as the latter are more folivorous and require to spend much time in resting to digest leaves (Kavana et al 2015). Prerna Singh (Singh 2017) observed abandonment of infants by Bonnet Macaque females after a group split, and reported that weaning may also occur without aggressive responses from mothers.…”
Section: University Of Mysore Mysurumentioning
confidence: 99%
“…For example, the females who are undergoing gestation and lactation will have to spend more energy on these reproductive activities and hence may modify their overall activity during these time periods [Bercovitch, 1987;McFarland, 1997]. Also, the enforced time constraints caused by physiological constraints such as the degree of folivory will affect the time activity budgets [Dunbar et al, 2009;Korstjens et al, 2010;Kavana et al, 2015] of a species. The interindividual differences in activities of individuals derived from activity budgets is important for assessing feeding competition and energetic constraints in a species [Isbell and Young, 2002;Ellis, 2012].…”
Section: Introductionmentioning
confidence: 99%
“…We assumed bonnet macaques occupying human-dominated habitats, where natural food resources are limited and variable individual skills are required to access food which most of the time is concealed [Mangalam and Singh, 2013], to be experiencing higher feeding competition and hence more variability among individuals, than liontailed macaques feeding on abundant and clumped natural resources at specific resource patches in a rain forest. Among the langurs of south India, it has been observed that a high degree of folivory is a constraint since langurs need to spend more time on resting, restricting the time available for the other activities [Kavana et al, 2015]. Also, it has been observed that Nilgiri langurs are more folivorous than black-footed grey langurs [Kavana et al, 2015], though both species primarily inhabit rain forests of south India.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation